Genome-Wide Comparative Analysis of the Phospholipase D Gene Families among Allotetraploid Cotton and Its Diploid Progenitors - Tang, Kai (PLoS One, 2016)
In this study, 40 phospholipase D (PLD) genes were identified from allotetraploid cotton Gossypium hirsutum, and 20 PLD genes were examined in diploid cotton Gossypium raimondii. Combining with 19 previously identified Gossypium arboreum PLD genes, a comparative analysis was performed among the PLD gene families among allotetraploid and two diploid cottons. Based on the orthologous relationships, we found that almost each G. hirsutum PLD had a corresponding homolog in the G. arboreum and G. raimondii genomes, except for GhPLDβ3A, whose homolog GaPLDβ3 may have been lost during the evolution of G. arboreum after the interspecific hybridization. Phylogenetic analysis showed that all of the cotton PLDs were unevenly classified into six numbered subgroups: α, β/γ, δ, ε, ζ and φ. An N-terminal C2 domain was found in the α, β/γ, δ and ε subgroups, while phox homology (PX) and pleckstrin homology (PH) domains were identified in the ζ subgroup. The subgroup φ possessed a single peptide instead of a functional domain. In each phylogenetic subgroup, the PLDs showed high conservation in gene structure and amino acid sequences in functional domains. The expansion of GhPLD and GrPLD gene families were mainly attributed to segmental duplication and partly attributed to tandem duplication. Furthermore, purifying selection played a critical role in the evolution of PLD genes in cotton. Quantitative RT-PCR documented that allotetraploid cotton PLD genes were broadly expressed and each had a unique spatial and developmental expression pattern, indicating their functional diversification in cotton growth and development. Further analysis of cis-regulatory elements elucidated transcriptional regulations and potential functions. Our comparative analysis provided valuable information for understanding the putative functions of the PLD genes in cotton fiber.